The Influence of Online Shop on Consumptive Behavior of IAIN Metro Sharia Economics Students - Anisa Aulia; Nur Syamsiyah (Peradaban Journal of Economic and Business, 2024)
The rapid development of information technology, especially the widespread use of the internet, has revolutionized various aspects of daily life by facilitating access to online platforms to fulfill individual needs. This convenience significantly influences consumer behavior, leading to increased consumption tendencies. This study aims to investigate the impact of online shops on the consumptive behavior of Islamic Economics students at IAIN Metro. Using a quantitative methodology, the research focuses on two main variables: online shop usage as the independent variable and consumer behavior as the dependent variable. The sample consists of 67 students selected using a proportional random sampling method. Data analysis was conducted using SPSS Statistics version 25, including validity and reliability testing, classical assumption tests, as well as simple linear regression and t-tests. The research findings indicate a significant influence of online shops on consumer behavior, with a t-test result of 6.736, exceeding the critical t-value of 1.997, and a significance value of 0.000 < 0.05. Thus, the null hypothesis (H_0) is rejected, while the alternative hypothesis (H_a) is accepted, demonstrating a clear relationship between online shop usage and the consumptive behavior of Islamic Economics students at IAIN Metro. Perkembangan pesat teknologi informasi, khususnya penggunaan internet yang luas, telah merevolusi berbagai aspek kehidupan sehari-hari dengan memudahkan akses ke platform online untuk memenuhi kebutuhan individu. Kenyamanan ini secara signifikan memengaruhi perilaku konsumen, yang mengarah pada kecenderungan konsumsi yang meningkat. Penelitian ini bertujuan untuk menyelidiki dampak toko online terhadap perilaku konsumtif mahasiswa Ekonomi Syariah di IAIN Metro. Dengan menggunakan metodologi kuantitatif, penelitian ini memusatkan perhatian pada dua variabel utama: penggunaan toko online sebagai variabel independen dan perilaku konsumen sebagai variabel dependen. Sampel terdiri dari 67 mahasiswa yang dipilih menggunakan metode pengambilan sampel acak proporsional. Analisis data dilakukan menggunakan SPSS Statistics versi 25, termasuk uji validitas dan reliabilitas, uji asumsi klasik, serta regresi linear sederhana dan uji-t. Hasil penelitian menunjukkan adanya pengaruh signifikan toko online terhadap perilaku konsumen, dengan hasil uji-t sebesar 6,736, melebihi nilai t kritis sebesar 1,997, dan nilai signifikansi 0,000 < 0,05. Dengan demikian, hipotesis nol (H_0) ditolak, sementara hipotesis alternatif (H_a) diterima, menunjukkan hubungan yang jelas antara penggunaan toko online dan perilaku konsumtif mahasiswa Ekonomi Syariah di IAIN Metro.